CD47 Knock‐Out Using CRISPR‐Cas9 RNA Lipid Nanocarriers Results in Reduced Mesenchymal Glioblastoma Growth In Vivo - Nadia Rouatbi; Adam A. Walters; Alaa Zam; Yau Mun Lim; Alessia Marrocu; Revadee Liam‐Or; Joanne E. Anstee; James N. Arnold; Julie Tzu‐Wen Wang; Steven M. Pollard; Khuloud T. Al‐Jamal (Advanced Science)
Abstract Immune checkpoint (ICP) blockade has shown limited effectiveness in glioblastoma (GBM), particularly in the mesenchymal subtype, where interactions between immune cells and glioblastoma cancer stem cells (GSCs) drive immunosuppression and therapy resistance. Tailoring ICPs specific to GSCs can enhance the antitumor immune response. This study proposes the use of lipid nanoparticles (LNPs) encapsulating CRISPR RNAs as an in vivo screening tool for ICPs in a syngeneic model of mesenchymal GSCs. Using PD‐L1 and CD47 to validate the proof of concept, intratumoral administration of LNPs in orthotopic tumors achieved efficient editing of ICPs, leading to enhanced immune cell infiltration within the tumor microenvironment. Targeting CD47 reduced tumor growth, suggesting improved cancer cell sensitization to the immune system post‐ICP editing. The study positions LNPs as a robust tool for in vivo validation of ICPs as therapeutic targets in clinically relevant GBM models. LNPs could serve as a screening tool in patient‐derived xenografts to identify and optimize ICP combinations, potentially expediting ICP translation and enhancing personalized GBM immunotherapies.